Analysis of Severe Accident in Complex System Reactor Using Moving Particle Semi-Implicit (MPS) Method - Rifqa Fikriya Rahasri; Asril Pramutadi Andi Mustari; Anni Nuril Hidayati (Jurnal Pengembangan Energi Nuklir, 2021)
The very complex structure of nuclear reactors is one aspect of the cause of severe accidents in nuclear reactors. To prevent serious accidents, analysis is needed on the reactor design before the reactor is built. Reactor accident analysis can be done using the Moving Particle Semi-Implicit method. The Moving Particle Semi-Implicit method is excellent in simulating the movement of liquid fuel in a reactor because it can analyze the free surface flow of an incompressible liquid without using a mesh grid. Simulations were carried out using three types of fluids with different viscosities and densities such as water, oil, and wax. The simulation results show that the water takes the fastest time to drain all the particles and the oil takes the longest time. From the simulation results, it can be determined that the kinematic viscosity of a liquid affects its flow velocity.